PHYSICAL, CHEMICAL AND MECHANICAL CHARACTERIZATION OF Acrocarpus fraxinifolius CULTIVATED IN SAO PAULO - de Oliveira, Karina A. [UNESP]; Oliveira, Carolina A. Barros [UNESP]; Molina, Julio C. [UNESP] (Universidad del Bio Bio, 2021)
Indian cedar (Acrocarpus fraxinifolius) is a wood species that occurs naturally in India, Myanmar (Burma) and Bangladesh, and has a high commercial value, with characteristics like mahogany and native cedars. The planting of Indian cedar has been undertaken in Brazil, but there is little information available regarding the characterization of the species. Therefore, considering its timber potential and its possibility of development in the country, the present work aimed to evaluate the physical, chemical, and mechanical properties of 9-year-old Indian cedar wood, planted in the southern region of Brazil. A low specific mass (502 kg/m³), low average dimensional stability (anisotropy coefficient of 2,09 %) was observed, in addition to the low content of extractives (1,94 %). From the mechanical characterization, an average value for the elastic modulus of 8963 MPa was obtained, and for the compressive strength parallel to the grain the average and characteristic values were 32,14 MPa and 21,46 MPa, respectively. This indicates that this wood belongs to resistance class C20 (dicotyledons). The results obtained classify the wood for use in light, external, or internal civil construction
Keywords: Acrocarpus fraxinifolius; Chemical properties; Indian cedar; Mechanical properties; Physical properties